2021
DOI: 10.3389/fcvm.2021.752305
|View full text |Cite
|
Sign up to set email alerts
|

Stressor-Induced “Inflammaging” of Vascular Smooth Muscle Cells via Nlrp3-Mediated Pro-inflammatory Auto-Loop

Abstract: Calcification of the vessel wall as one structural pathology of aged vessels is associated with high cardiovascular mortality of elderly patients. Aging is linked to chronic sterile inflammation and high burden of reactive oxygen species (ROS), leading to activation of pattern recognition receptors (PRRs) such as Nlrp3 in vascular cells. The current study investigates the role of PRR activation in the calcification of vascular smooth muscle cells (VSMCs). Therefore, in vitro cell culture of primary rat VSMCs a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 47 publications
1
10
0
Order By: Relevance
“…Multiplexing on a single cell level not only allows reduction of primary cells in the thought of the ThreeR (3R), referring to the guiding principles “Replace, Reduce, Refine” for more ethical use of animals for scientific research formulated by Russel and Burch [ 13 ], but also permits a direct comparison of the markers of interest in the signaling cascade in one cell [ 14 ]. As already known from our own and others’ previous studies, doxorubicin is a potent inducer of DNA damage and calcification in VSMC and was therefore used as a positive control [ 12 , 14 , 15 ], in addition to the stimulation of cells with COM and CAM as before.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Multiplexing on a single cell level not only allows reduction of primary cells in the thought of the ThreeR (3R), referring to the guiding principles “Replace, Reduce, Refine” for more ethical use of animals for scientific research formulated by Russel and Burch [ 13 ], but also permits a direct comparison of the markers of interest in the signaling cascade in one cell [ 14 ]. As already known from our own and others’ previous studies, doxorubicin is a potent inducer of DNA damage and calcification in VSMC and was therefore used as a positive control [ 12 , 14 , 15 ], in addition to the stimulation of cells with COM and CAM as before.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, co-staining of several markers, e.g., DNA damage via γH2A.X, allows single-cell-based visualization and direct comparison of, e.g., a senescence or osteogenic marker in a single cell with HAP crystals surrounding the cell [ 14 ]. For induction of DNA damage, the known inducer doxorubicin was used [ 12 , 14 , 15 ]. The combination of OsteoSense™ detection with other fluorescence-labeled senescence or osteogenic markers is also possible and therefore offers advantages concerning a reduced primary cell consumption according to the 3R principles [ 13 ] and additional experimental read out information.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, studies have shown that the pathways of Il-1β and Il-6 are interconnected [ 36 ]. Recently, we could show that Il-6 is induced during calcification progression, but not directly induces mineralization, while Il-1β induces an osteogenic driven auto-loop in smooth muscle cells [ 37 ]. Il-1β and Il-6 are known middle-sized uremic toxins influencing osteogenic differentiation [ 9 ].…”
Section: Discussionmentioning
confidence: 99%
“…The activated caspase-1 then promotes the maturation and release of interleukin (IL)-1β and IL-18, and induces the synthesis of more amount of inflammatory factors, such as IL-6 and tumor necrosis factor (TNF)-α, thus leading to an inflammatory cascade response ( 15 , 16 ). Moreover, activated caspase-1 can shear and activate Gasdermin D (GSDMD) protein, causing pyroptosis and aggravating mitochondrial damage ( 17 ). Recent studies in heart failure with preserved ejection fraction mice model and Sirt3-KO mice demonstrated that mitochondrial overacetylation promotes ASC aggregation into perinuclear mitochondria and NLRP3 inflammasome formation, implying that NLRP3 inflammasome activation is sensitive to mitochondrial function ( 18 ).…”
Section: Introductionmentioning
confidence: 99%